EFFECTIVENESS OF LOTUS PHYTOREMEDIATION (NYMPHAEA PUBESCENS) IN REDUCING AMMONIA AND PHOSPHATE CONCENTRATIONS IN COFFEE LIQUID WASTE - Bariroh, Ghurrotul; Ulfah, Maria; Prasetiyo (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Based on laboratory tests of ammonia and phosphate concentrations in coffee wastewater from coffee factory in Semarang, the concentrations were found to be 8.55 and 1.01 mg/L, respectively. These high concentrations negatively impact fish farming production. Nymphaea pubescens has shown potential in remediating ammonia and phosphate concentrations in coffee wastewater. Therefore, the objective of this study is to determine the effectiveness of lotus phytoremediation (Nymphaea pubescens) in reducing ammonia and phosphate concentrations in coffee wastewater. The research method employed is true experiment with Completely Randomized Design, involving four treatments and three replications. According to ANOVA and Duncan's Multiple Range Test results, Nymphaea pubescens significantly reduced ammonia and phosphate concentrations in coffee wastewater. So far there have been no specific studies on the phytoremediation of Nymphaea pubescens for ammonia and phosphate concentrations in coffee wastewater, making this study a novel contribution. The findings suggest that this approach should be widely implemented, especially within educational settings and communities.